Лингвистический портрет десятилетия Lingvistitseskij portret desjatiletija - Budanova Tamara (Universitatea Babes-Bolyai, 2022)
Linguistic portrait of the decade. This article presents and briefly discusses the lists Words of the Year published annually from 2007 to 2018 in Russia. The Words of the Year have been selected by the vote of independent linguists. These lists include the most important words or expressions in the public sphere during a specific year..
Lucrările simpozionului internaţional „100 de ani de slavistică la Cluj” Cluj-Napoca, 30-31 mai 2019